Implementasi Model Pembelajaran Berbasis Proyek pada Mata Pelajaran IPS di MTs. Negeri 1 Jember Tahun Pelajaran 2019/2020 - Ayu Gita Lestari (Institut Agama Islam Negeri Jember, 2021)
As a matter of fact, social lesson must be done as fun as possible through an activity which are full of fun, spirit, enthusiastic and value that create better student development. Therefore, those need a suitable learning model for students. The purpose of this research is to know how the implementation of learning modelbased project toward social lesson in MTsN 1 Jember. The approach of this research is using field research. The data collections are using interview, observation and documentation. The analysis technic used from Miles’ and Huberman’s data’s includes data condensation, data presentation, conclusion, and verification. The result found from this research is that the implementation of learning model based project in the 9th class of MTsN 1 Jember is able to enhance students’ spirit and enthusiastic in learning social lesson. It is proven by students’ social lesson better score which is above average with score ranges are 85-95.